2001
DOI: 10.1046/j.1464-410x.2001.02191.x
|View full text |Cite
|
Sign up to set email alerts
|

Are dietary influences on the risk of prostate cancer mediated through the insulin‐like growth factor system?

Abstract: Objectives To investigate whether dietary factors that appear to affect the risk of prostate cancer may be similarly associated with serum levels of insulin-like growth factor 1 (IGF-1). Patients and methods In the context of a case-control study, 112 men were admitted to three teaching hospitals in Athens, Greece, for disorders other than cancer. Sociodemographic data and detailed histories of smoking, alcohol and coffee consumption were recorded. A validated food-frequency questionnaire was administered by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 46 publications
8
55
2
3
Order By: Relevance
“…Both energy and protein are needed to restore IGF-I after fasting [11]. Our results, in a study population with adequate intake of energy and protein, are consistent with most previous cross-sectional studies, in which no association between energy and protein intake and circulating IGF-I and IGFBP-3 was observed [12][13][14][15][16][17][18][19][20]. The two largest cross-sectional studies did show a positive association between IGF-I and protein intake within the normal range [22,23], as is also found by two smaller studies [21,24].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Both energy and protein are needed to restore IGF-I after fasting [11]. Our results, in a study population with adequate intake of energy and protein, are consistent with most previous cross-sectional studies, in which no association between energy and protein intake and circulating IGF-I and IGFBP-3 was observed [12][13][14][15][16][17][18][19][20]. The two largest cross-sectional studies did show a positive association between IGF-I and protein intake within the normal range [22,23], as is also found by two smaller studies [21,24].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that higher alcohol intake was associated with decreased IGFBP-1 concentrations in postmenopausal women. Cross-sectional studies on the association between alcohol intake and the IGF-system published to date have not investigated IGFBP-1, and have been very inconsistent with respect to IGF-I and IGFBP-3 [14,15,17,22,26]. This may be partly explained by the different ranges of intakes studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations